Crystallization test: A prognostic biomarker in oral potentially malignant disorders and oral cancer - Kinjal Joshi; Jigna Shah (Indian Journal of Pathology and Microbiology)
Aim: The aim of study is to evaluate the crystallization pattern seen in cupric chloride medium using haemolyzed blood of control, Oral potentially malignant disorders (OPMDs) and oral squamous cell carcinoma (OSCC) patients. Materials and Methods: Study comprise 90 patients including control, OPMDs and OSCC. To create a haemolysed blood, a drop of blood was obtained and distilled water was added. Crystallization test using 0.1 ml of haemolyzed blood and 20% of a 10 ml cupric chloride solution. During 24 to 28 hours, this solution was put in a BOD incubator. Result: Crystallization pattern in control group is eccentric placed nucleus and peripheral radiating lines while in OPMDs and OSCC presence of transverse bar. Crystallization test showed 100% positivity in OSCC while 73.33% seen in control group. 90% sensitivity in OSCC and 76.67% sensitivity in OPMDs. Conclusion: OPMDs lesion convert from white to mixed red and white lesion and OSCC appear as non-healing ulcer or ulcero-proliferative growth increase in number of transverse bars. More number of transverse bars suggestive of high malignant potential.